Odpowiedź :
x²-(x-6)²=-120
x²-(x²-12x+36)=-120
x²-x²+12x-36=-120
12x=-120+36
12x=-84 /:12
x=-7
x²-(x²-12x+36)=-120
x²-x²+12x-36=-120
12x=-120+36
12x=-84 /:12
x=-7
x^2 - (x-6)^2 = -120
x^2 - (x^2 +36 -12x) = -120
x^2 - x^2 - 36 +12x = 120
-36 +12x = 120 / + 36
12x = -84 / 12
x = -7
x^2 - (x^2 +36 -12x) = -120
x^2 - x^2 - 36 +12x = 120
-36 +12x = 120 / + 36
12x = -84 / 12
x = -7
a² -(a-6)² = -120
a² - (a²-12a+36) = -120
a² - a² + 12a - 36 = -120 // +36
12a = -84 // :12
a = -7
a² - (a²-12a+36) = -120
a² - a² + 12a - 36 = -120 // +36
12a = -84 // :12
a = -7